Midwives' role in the provision of maternal and childhood immunisation information. Issue 2 (March 2020) - Frawley, Jane E.; McKenzie, Kirsty; Cummins, Allison; Sinclair, Lynn; Wardle, Jon; Hall, Helen
Abstract: Problem: Inactivated influenza vaccine and diphtheria-tetanus acellular pertussis vaccine are routinely recommended during pregnancy to protect women and their babies from infection. Additionally, the hepatitis B vaccine is recommended for infants within the first week of life; however, little is known about midwives' experiences of recommending and delivering these immunisations. Background: Midwives are a trusted source of vaccine information for parents and the confident provision of information about immunisation during antenatal clinic visits has been found to increase the uptake of antenatal and childhood vaccines. Aim: This study aims to explore midwives' experiences of discussing maternal and childhood immunisation with women and their partners and their confidence in answering parent's questions. Methods: We conducted 23 semi-structured interviews with registered Australian midwives working in public and private hospital settings, and in private practice. Findings: Midwives find negotiating the requirement to recommend immunisation within a women-centred framework challenging at times. The vast majority of midwives described their education on immunisation as inadequate and workplace issues, such as time pressure, were identified as further barriers to effective communication about immunisation. Discussion/conclusion: The provision of immunisation training within midwifery education and continued professional development is critical. Appropriately resourcing midwives with the necessary infrastructure, education and resources to fully inform parents about immunisation may have a positive impact on vaccine uptake.